2007
DOI: 10.1111/j.1464-410x.2007.06931.x
|View full text |Cite
|
Sign up to set email alerts
|

The type 1 insulin‐like growth factor receptor is over‐expressed in bladder cancer

Abstract: OBJECTIVE To analyse bladder cancer biopsies and investigate the pattern of expression of the type 1 insulin‐like growth factor receptor (IGF1R), a receptor tyrosine kinase that mediates tumour cell proliferation, motility and protection from apoptosis. MATERIALS AND METHODS Formalin‐fixed specimens of bladder cancer (40 whole‐mount, 80 cores on a tumour microarray) and normal bladder (15 samples) were stained immunohistochemically for the IGF1R. The IGF1R expression was also measured by quantitative reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…There are currently approximately 12 anti-IGF-IR therapeutic agents undergoing clinical evaluation, including blocking antibodies and tyrosine kinase inhibitors (small molecules). The complete list of anti-IGF-IR therapeutics is summarized in a recent review by Chitnis et al 16 A definite role for the IGF-IR in transformation of urothelial cells is not clearly established, but Rochester et al 18 recently reported that the IGF-IR is up-regulated in bladder cancer tissues compared with nonmalignant tissue controls. They also showed by quantitative real-time poly- merase chain reaction (RT-PCR) that IGF-IR mRNA levels were significantly increased in invasive cancers compared with normal urothelium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are currently approximately 12 anti-IGF-IR therapeutic agents undergoing clinical evaluation, including blocking antibodies and tyrosine kinase inhibitors (small molecules). The complete list of anti-IGF-IR therapeutics is summarized in a recent review by Chitnis et al 16 A definite role for the IGF-IR in transformation of urothelial cells is not clearly established, but Rochester et al 18 recently reported that the IGF-IR is up-regulated in bladder cancer tissues compared with nonmalignant tissue controls. They also showed by quantitative real-time poly- merase chain reaction (RT-PCR) that IGF-IR mRNA levels were significantly increased in invasive cancers compared with normal urothelium.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Whether the IGF-IR contributes to the transforming phenotype of urothelial cells has not been clearly established, but recent data suggest that the IGF-IR is overexpressed in bladder cancer. 18 In this study, using 5637 and T24 urothelial carcinomaderived cells, we established that activation of the IGF-IR plays a critical role in bladder cancer by promoting migration, wound healing, and invasion of cancer urothelial cells. We have also characterized the mechanism of action of the IGF-IR in cancer urothelial cells and showed that IGF-IR-dependent cell motility and invasion required the activation of the Akt and MAPK pathway and Akt-and Extracellular-signal-related kinase 1 (ERK)-dependent activation of paxillin.…”
Section: -15mentioning
confidence: 91%
See 1 more Smart Citation
“…Although it is difficult to directly compare between cell lines due to karyotypic variability, it was surprising that IGF-II expression levels were lowest in the mesenchymal IGF-II LOI TCCSUP cell line, with higher levels being observed in the epithelial IGF-II MOI RT4 cell line. The IGF-I receptor has been shown to be significantly up-regulated in superficial and invasive UCB compared with normal urothelium (33), with a close relationship existing between IGF-I receptor and stage, grade, and recurrence (34). Reinforcing the suggestion that IGF-II LOI may effect IGF-I receptor expression (10), the undifferentiated TCCSUP IGF-II LOI cell line has been shown to have significantly more IGF-I receptor than the differentiated RT4 IGF-II MOI cell line (35).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-143 levels in human blood and tumor tissues are associated with cancer occurrence, metastasis and drug resistance (15), indicating the potential of miR-143 as a biomarker. The role of IGF-1R in cancerous transformation of urothelial cells is not well established, but previous studies have demonstrated that IGF-1R is overexpressed in bladder cancer (16). Given the interrelationship between IGF-1R and miR-143, we speculate that downregulation of miR-143 in bladder cancer may be involved in tumor development via the activation of IGF-1R and other downstream pathways (e.g.…”
Section: Introductionmentioning
confidence: 98%